A longitudinal diffusion tensor imaging study in symptomatic Huntington's disease. Issue 3 (22nd February 2009) - Sritharan, Anusha; Egan, Gary F; Johnston, Leigh; Horne, Malcolm; Bradshaw, John L; Bohanna, India; Asadi, Hamed; Cunnington, Ross; Churchyard, Andrew J; Chua, Phyllis; Farrow, Maree; Georgiou-Karistianis, Nellie
Abstract : Objective: The striatum and its projections are thought to be the earliest sites of Huntington's disease (HD) pathology. This study aimed to investigate progression of striatal pathology in symptomatic HD using diffusion tensor imaging. Method: Diffusion weighted images were acquired in 18 HD patients and in 17 healthy controls twice, 1 year apart. Mean diffusivity (MD) was calculated in the caudate, putamen, thalamus and corpus callosum, and compared between groups. In addition, caudate width was measured using T1 high resolution images and correlated with caudate MD. Correlation analyses were also performed in HD between caudate/putamen MD and clinical measures. Results: MD was significantly higher in the caudate and putamen bilaterally for patients compared with controls at both time points although there were no significant MD differences in the thalamus or corpus callosum. For both groups, MD did not change significantly in any region from baseline to year 1. There was a significant negative correlation between caudate width and MD in patients at baseline but no correlation between these parameters in controls. There was also a significant negative correlation between Mini-Mental State Examination scores and caudate MD and putamen MD at both time points in HD. Conclusions: It appears that microstructural changes influence cognitive status in HD. Although MD was significantly higher in HD compared with controls at both time points, there were no longitudinal changes in either group. This finding does not rule out the possibility that MD could be a sensitive biomarker for detecting early change in preclinical HD.